Online position control system using incremental fuzzy control - Wan Abas, Wan Hamidah (2014)
In the field of fuzzy control theory, fuzzy logic controllers is one of the most active research areas and are particularly useful in controlling various types of physical processes. Therefore, this project also involved in usage of the fuzzy logic controller. Main objective of this project is to develop online position control of DC motor using Incremental Fuzzy Logic Controller (IFLC). The IFLC were developed by using MATLAB Simulink and implemented in the real position control system hardware. RAPCON platform is a hardware that was implemented in real-time session with DC motor. For simulation, signal generator used as the reference input in the form of square wave. The best gains used for the IFLC in simulation are: gain of error (GE) is 2.721, gain of change error (GCE) is 0.019 and gain of output (GCU) is 0.259. While real-time simulation use the most gains such as gain error (GE) of 1.785, gain of change error (GCE) is 0.0056955 and gain of output (GCU) is 0.01. Both method either simulation or real-time generate in 20 seconds. The result was obtained in form of graph and their performance was analysed. Based on the result, the IFLC shows the better performance of the overshoot percentage (%OS) of 0%.